Out of sight, out of mind! Bank branch closures and new firm creation in Italy - Paola Cardamone; Francesco Trivieri (Regional Studies, Regional Science, 2024)
Building on the literature underscoring the importance of lending relationships and the role of banks’ structural and organisational features in favouring firms’ access to credit, we investigate the effect of branch closures on firms’ birth rates in the Italian local credit markets in 2000–2020. Despite the potential relevance, the implications of de-branching activity have received modest attention from scholars thus far. By employing various measures of branch closures and econometric methodologies, we find that the de-branching process negatively affects the establishment of new firms, and this detrimental impact appears stronger as the closures involve older branches. The results also show that our main findings seem ascribable to the closures carried out by large/medium-sized banks. As a policy implication, our work suggests that – although driven by technological transformations and banks’ necessity to rationalise costs – authorities should consider the potential negative consequences that bank de-branching may entail for new business creation.